Change of Occupational Health and Safety (OHS) University Students' Perceptions on OHS in Parallel to Vocational Training: The Comparative Analysis - Derya Çevik Taşdemir; Güfte Caner Akın (Üniversite Araştırmaları Dergisi)
The curricula at universities were also positively affected by the "Occupational Health and Safety", which gained importance in recent years within the scope of the ILO directives that came into force, and courses related to the field were added to the curriculum. The aim of this study; To measure and analyze the level of knowledge and awareness of students about Occupational Health and Safety (OHS). In this context, the sample of the research is in Turkey; Istanbul Gelisim University, which is a foundation university, and Gaziantep University, which is a state university, consist of the Occupational Health and Safety program students. Data were collected through a questionnaire created within the scope of the study. The questionnaire consists of demographic questions and questions about the OHS Awareness Scale. In the research, the data were analyzed by using the SPSS 25.0 statistical package program. The scale questions used in this study were collected in a single factor, unlike the original scale. As a result of the study, it has been seen that the presence of a laboratory where applied courses can take place at the university where the students receive OHS education and the fact that their parents are employers positively predict OHS awareness. This study is important in terms of evaluating the workplace safety culture perspectives that students have about Occupational Health and Safety legal practices within the framework of ILO directives and revealing their perspectives on the effectiveness of occupational health and safety education.